2010
DOI: 10.1103/physrevb.81.064419
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetism inSnO2-based multilayers: Clustering of defects induced by doping

Abstract: Several series of A / SnO 2 and Mn/B multilayers, where A and B are thin layers ͑0.4-10.1 nm͒ of SnO 2 , SiO 2 , Si, Al, Mn, or MnO x , have been investigated magnetic, electronic, and structurally. The study demonstrates that the detected ferromagnetism is related to regions of high density of defects in SnO 2 induced by doping under particular conditions. The observed room-temperature ferromagnetic ͑RTFM͒ signal does not scale to Mn content but increases with the number of interfaces and their roughness. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…In recent years tin oxides, pure and doped, have been advancing over a broad front in nanoscience and nanotechnology: in optoelectronics, photovoltaics, magnetism, gas sensing, and catalysis. Out of several possible tin oxides, the one most used is tin­(IV) oxide, SnO 2 , which is a wide-gap semiconductor with natural n-type conductivity. This conductivity has been, as a rule, assigned to the “effective” oxidation state caused by substantial oxygen deficiency in the crystal lattice. , At the same time the other stable oxide form, tin­(II) oxide, SnO, has p-type conductivity, , and metal-atom deficiency has been observed in it . Some intermediate/nonstoichiometric tin oxides, SnO x (1 < x < 2), are also known and have been reported to have either p- or n-type conductivity. , All these tin oxides may coexist in laboratory-prepared samples, and the sample composition is strongly dependent on the preparation method.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years tin oxides, pure and doped, have been advancing over a broad front in nanoscience and nanotechnology: in optoelectronics, photovoltaics, magnetism, gas sensing, and catalysis. Out of several possible tin oxides, the one most used is tin­(IV) oxide, SnO 2 , which is a wide-gap semiconductor with natural n-type conductivity. This conductivity has been, as a rule, assigned to the “effective” oxidation state caused by substantial oxygen deficiency in the crystal lattice. , At the same time the other stable oxide form, tin­(II) oxide, SnO, has p-type conductivity, , and metal-atom deficiency has been observed in it . Some intermediate/nonstoichiometric tin oxides, SnO x (1 < x < 2), are also known and have been reported to have either p- or n-type conductivity. , All these tin oxides may coexist in laboratory-prepared samples, and the sample composition is strongly dependent on the preparation method.…”
Section: Introductionmentioning
confidence: 99%
“…Among the universe of materials, oxides exhibit unique structural, electronic, and magnetic properties and possess an exceptional potential as base materials in a broad range of industrial and technological applications including optical, electronic, optoelectronic, and biological fields. Particularly, rutile-type tin dioxide (SnO 2 ) is maybe one of the most studied metallic oxide , and have attracted a renewed interest. SnO 2 is a direct n -type semiconductor (a band gap of 3.6 eV, refs and ) that presents high electrical conductivity and transmittance in the ultraviolet–visible region and infrared reflectance. , Its n-type electrical conductivity is originated by intrinsic defects (oxygen vacancies and tin interstitials). The occurrence of transparency and conductivity makes it a suitable candidate for application as an optically passive component in optoelectronic devices such as solar cells, , touch screens, transparent electrodes, solid-state chemical and gas sensors, , catalytic support, secondary lithium battery electrodes, and potential candidates for spintronic devices. , …”
Section: Introductionmentioning
confidence: 99%
“…For example, Nb‐doping of anatase TiO 2 leads to magnetic moments induced by cation vacancies . Similarly, it has been shown that ferromagnetism in SnO 2 ‐based multilayers is related to defect clustering induced by doping …”
Section: Introductionmentioning
confidence: 99%